Studies on ZnO based diluted magnetic semiconductors - Deka, Sasanka; Joy, P. A. (TMS 2008 Annual Meeting Supplemental Proceedings, 2008)
The observation of ferromagnetism in the transition metal (TM) doped wide band gap nonmagnetic semiconductor ZnO opened up a new area of research because of the potential applications in spintronics devices. These ZnO based diluted magnetic semiconductors (DMS) combine their transport and optical properties with magnetism. We have carried out synthesis and studies on the magnetic and optical properties on TM doped ZnO powders in nanocrystalline form. Our studies give evidence for the origin of ferromagnetism as extrinsic due to the presence of metal nanoclusters as secondary phases in the Co and Ni doped ZnO systems although the optical and electronic structure studies indicate the incorporation of divalent metal ions inside the ZnO crystal lattice.

Magnetic and magnetostrictive properties of aluminium substituted cobalt ferrite synthesized by citrate-gel method - Anantharamaiah, P. N.; Joy, P. A. (Journal Of Materials Science, 2015)
Structural, magnetic and magnetostrictive properties of sintered aluminium-substituted cobalt ferrite, CoAlxFe2-xO4 (x = 0.0, 0.1, 0.20, 0.30), derived from nanosized powders synthesized by a citrate-gel method, have been investigated. The sample with x = 0.1 is found to exhibit higher maximum magnetostriction strain at relatively lower magnetic fields (230 ppm at 286 kA/m) than that obtained for the unsubstituted cobalt ferrite (217 ppm, at 446 kA/m). All the Al-substituted compositions show larger strain sensitivity (d lambda/dH) at low magnetic fields compared to that for the unsubstituted cobalt ferrite. The variation of the magnetostriction coefficient as well as the strain sensitivity with Al content is likely to be due to the changes in the cation distribution in the tetrahedral and octahedral sites of the spinel lattice along with the associated changes in the magnetocrystalline anisotropy. The magnetostriction coefficient of x = 0.1 could be further enhanced to 306 ppm (at 220 kA/m) after a magnetic field annealing at 300 degrees C. A very high strain sensitivity of 4.5 x 10(-9) m/A is obtained for the magnetically annealed sample, larger than that reported for any substituted cobalt ferrite samples. The combination of high magnetostriction coefficient and strain sensitivity is suitable for device applications.

Defect induced modification of structural, topographical and magnetic properties of zinc ferrite thin films by swift heavy ion irradiation - Raghavan, Lisha; Joy, P. A.; Vijaykumar, B. Varma; Ramanujan, R. V.; Anantharaman, M. R. (Nuclear Instruments & Methods In Physics Research Section B-Beam Interactions With Materials And Atoms, 2017)
Swift heavy ion irradiation provides unique ways to modify physical and chemical properties of materials. In ferrites, the magnetic properties can change significantly as a result of swift heavy ion irradiation. Zinc ferrite is an antiferromagnet with a Neel temperature of 10 K and exhibits anomalous magnetic properties in the nano regime. Ion irradiation can cause amorphisation of zinc ferrite thin films; thus the role of crystallinity on magnetic properties can be examined. The influence of surface topography in these thin films can also be studied. Zinc ferrite thin films, of thickness 320 nm, prepared by RF sputtering were irradiated with 100 MeV Ag ions. Structural characterization showed amorphisation and subsequent reduction in particle size. The change in magnetic properties due to irradiation was correlated with structural and topographical effects of ion irradiation. A rough estimation of ion track radius is done from the magnetic studies. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Spin glass; Swift heavy ion; Zinc Ferrite

Docetaxel-titanate nanotubes enhance radiosensitivity in an androgen-independent prostate cancer model - Mirjolet, C.; Martin, E.; Boudon, J.; Loiseau, A.; Chevrier, S.; Boidot, R.; Oudot, A.; Collin, B.; Joy, P. A.; Millot, N.; Créhange, G. (International Journal of Nanomedicine, 2017)
Around 40% of high-risk prostate cancer patients who undergo radiotherapy (RT) will experience biochemical failure. Chemotherapy, such as docetaxel (DTX), can enhance the efficacy of RT. Multidrug resistance mechanisms often limit drug efficacy by decreasing intracellular concentrations of drugs in tumor cells. It is, therefore, of interest to develop nanocarriers of DTX to maintain the drug inside cancer cells and thus improve treatment efficacy. The purpose of this study was to investigate the use of titanate nanotubes (TiONts) to develop a TiONts-DTX nanocarrier and to evaluate its radiosensitizing in vivo efficacy in a prostate cancer model. In vitro cytotoxic activity of TiONts-DTX was evaluated using an MTS assay. The biodistribution of TiONts-DTX was analyzed in vivo by single-photon emission computed tomography. The benefit of TiONts-DTX associated with RT was evaluated in vivo. Eight groups with seven mice in each were used to evaluate the efficacy of the nanohybrid combined with RT: control with buffer IT injection ± RT, free DXL ± RT, TiONts ± RT and TiONts-DXL ± RT. Mouse behavior, health status and tumor volume were monitored twice a week until the tumor volume reached a maximum of 2,000 mm3. More than 70% of nanohybrids were localized inside the tumor 96 h after administration. Tumor growth was significantly slowed by TiONts-DTX associated with RT, compared with free DTX in the same conditions (P=0.013). These results suggest that TiONts-DTX improved RT efficacy and might enhance local control in high-risk localized prostate cancer.
Keywords: Docetaxel Nanocarrier; nanoparticle; Prostate Cancer; Radiosensitivity; Titanate nanotubes

Effect of size and site preference of trivalent non-magnetic metal ions (Al3+, Ga3+, In3+) substituted for Fe3+ on the magnetostrictive properties of sintered CoFe2O4 - Anantharamaiah, P. N.; Joy, P. A. (Journal of Physics D-Applied Physics, 2017)
The influence of size and crystallographic site preference of three non-magnetic isovalent metal ions of larger (In3+), comparable (Ga3+) and smaller (Al3+) sizes, substituted for Fe3+ in the spinel lattice of CoFe2O4 on its magnetostrictive properties is compared. For the different compositions in CoFe2-xMxO4 (M = In3+, Ga3+, Al3+ and 0 <= x <= 0.3), significant changes in the structural and magnetic parameters are observed with the degree of substitution, due to the size and site preferences. Magnetic and Raman spectral studies revealed that Al3+ is substituted for Fe3+ at both octahedral and tetrahedral sites for all compositions, whereas In3+ and Ga3+ are substituted for Fe3+ at the tetrahedral site only for x <= 0.2 and partly at the octahedral site for x > 0.2. Regardless of the differences in the ionic size, site preference and the magnetic properties, compositions in all three series with x = 0.1 showed almost equal magnitude of maximum magnetostriction (lambda(max) = similar to 230 ppm), marginally higher than that of x = 0 (217 ppm). However, at higher substituted compositions, lambda(max) is decreased with x, but the decrease is much faster for the Al-substituted compositions. The maximum strain sensitivity, [d lambda/dH](max), is also found to be comparable for all three compositions. The comparable magnetostriction characteristics and high strain at low magnetic fields for different substituted compositions at low levels of substitution are attributed to the local structural distortions associated with the inhomogeneous distribution of the substituted ions in the spinel ferrite lattice. The studies suggest ways to optimise the magnetostriction properties of properly substituted sintered cobalt ferrite for applications in sensors and actuators.

High magnetostriction parameters of sintered and magnetic field annealed Ga-substituted CoFe2O4 - Anantharamaiah, P. N.; Joy, P. A. (Materials Letters, 2017)
Impact of substitution of the non-magnetic ion Ga3+ for Fe3+ on the magnetostriction parameters of CoFe2O4 has been investigated for samples prepared by a tartrate-gel method. All the Ga-substituted compositions in CoGaxFe2-xO4 (0 <= x <= 0.3) showed higher strain sensitivity (d lambda/dH), at low magnetic fields, compared to that of the unsubstituted sample. The magnetostriction strain (lambda) and d lambda/dH of the composition CoGa0.1Fe1.9O4 could be enhanced from -228 to -296 ppm and -2.20 x 10(-9) to -3.55 x 10(-9) miA, respectively, at low magnetic fields, after magnetic field annealing at 300 degrees C. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Cobalt ferrite; Magnetic field annealing; Magnetic materials; Magnetostriction; Substitution

Structural, magnetic, dielectric and magnetodielectric properties of Bi1-xCaxFe1-xMnxO3 in the morphotropic phase boundary region - Manjunath, B.; Thakuria, P.; Joy, P. A. (Materials Research Express, 2017)
Structural, magnetic, dielectric and magnetodielectric properties of Ca and Mn co-substituted bismuth ferrite, Bi1-xCaxFe1-xMnxO3 (0 <= x <= 0.4) are reported. Structural studies by Rietveld refinement of XRD patterns revealed rhombohedral R3c structure for x <= 0.11 and orthorhombic Pbnm structure for x >= 0.2. For compositions in the range 0.11 < x < 0.2, mixed phase behaviour is observed showing a morphotropic phase boundary (MPB) region. Magnetisation at room temperature increases with increasing Ca and Mn content, showing weak ferromagnetism. Coercivity and remanence initially increase and then decrease with increasing x, showing a maximum for x = 0.175 in the MPB region. Dielectric constant also shows a maximum value in the mixed phase region. Magnetodielectric (MD) studies revealed positive MD for the R3c phase and a negative MD for the Pbnm phase, showing a maximum MD (similar to 1%) for x approximate to 0.1 and crossover at x approximate to 0.175. The studies show strong interplay between the structure and properties, suggesting tuneable bismuth ferrite based compositions for magnetoelectric applications.

Tuning of the magnetostrictive properties of cobalt ferrite by forced distribution of substituted divalent metal ions at different crystallographic sites - Anantharamaiah, P. N.; Joy, P. A. (Journal of Applied Physics, 2017)
Comparative studies have been made to understand the role of different crystallographic site preferences of the substituted non-magnetic divalent metal ions in the magnetostrictive properties of cobalt ferrite, by substitution of Zn2+ and/or Mg2+ for Fe3+ in CoMgxFe2-xO4, CoZnxFe2-xO4, and CoMgx/2Znx/2Fe2-xO4 (0.0 <= x <= 0.2). Detailed Raman spectral and magnetic characterizations are made to extract the information on the tetrahedral/octahedral site preferences of Zn and Mg in the spinel lattice of cobalt ferrite. The structural, microstructural, magnetic, Raman spectral, and magnetostrictive parameters of the studied compositions show distinguishable variations for x< 0.1 and x >= 0.1. Co-substitution of a small amount of Mg and Zn for Fe in CoMgx/2Znx/2Fe2-xO4 (x < 0.1) showed relatively larger strain sensitivity, [d lambda/dH](max) (-2.6 x 10(-9) mA(-1) for x = 0.05), higher than that for the Mg-substituted samples (-2.05 x 10(-9) mA(-1) for x = 0.05) and comparable to that for the Zn-substituted samples (-2.47 x 10(-9) mA(-1) for x = 0.05), without much drop in the maximum value of magnetostriction, lambda(max) (-189 ppm for x = 0.05) compared to that for the unsubstituted counterpart (-221 ppm). The results show that it is possible to obtain high strain sensitivity (at fields < 50 kA/m), along with high magnetostriction strain at low magnetic fields (similar to 250 kA/m), by tuning the distribution of the substituted cations in the tetrahedral and octahedral sites of the cobalt ferrite lattice. Published by AIP Publishing.

Enhanced strain sensitivity in magnetostrictive spinel ferrite Co1-xZnxFe2O - Bhame, Shekhar D.; Joy, P. A. (Journal of Magnetism and Magnetic Materials, 2018)
We report the magnetic and magnetoelastic properties of spinel oxide system Co1-xZnxFe2O4 (CZF series) where x = 0.0, 0.1, 0.2, 0.3, 0.4, and 0.5. All the composition were prepared by conventional solid state synthesis method and exhibited pure spinel phase formation. The lattice parameters showed gradual increase indicating uniform distribution Zn ions in cobalt ferrite lattice. The magnetic properties such as saturation magnetization and coercive field were drastically affected with Zn substitution showing enhanced saturation magnetization and a sharp decrease in the coercivity. The room temperature magnetostrictive properties showed a promising 30% enhancement in the slope of magnetostriction curve for x = 0.2 composition and a reasonable magnetostrictive strain of 110 ppm indicating its suitability as a promising magnetostrictive material. (c) 2017 Elsevier B.V. All rights reserved.

Magnetically tunable liquid dielectric with giant dielectric permittivity based on core-shell superparamagnetic iron oxide - Vinayasree, S.; Nitha, T. S.; Tiwary, C. S.; Ajayan, P. M.; Joy, P. A.; Anantharaman, M. R. (Nanotechnology, 2018)
A liquid dielectric based on a core-shell architecture having a superparamagnetic iron oxide core and a shell of silicon dioxide was synthesized. The frequency dependence of dielectric properties was evaluated for different concentrations of iron oxide. The dependence of magnetic field on the dielectric properties was also studied. Aqueous ferrofluid exhibited a giant dielectric constant of 6.4 x 10(5) at 0.1 MHz at a concentration of 0.2 vol% and the loss tangent was 3. The large rise in dielectric constant at room temperature is modelled and explained using percolation theory and Maxwell-Wagner-Sillars type polarization. The ferrofluid is presumed to consist of nanocapacitor networks which are wired in series along the lateral direction and parallel along longitudinal direction. On the application of an external magnetic field, the chain formation and its alignment results in the variation of dielectric permittivity.

Structural and magnetic properties of La2Ni1-xCoxMnO6 compounds - Pramanik, Debabrata; Mukherjee, S.; Dan, Shovan; Nandy, A.; Pradhan, S. K.; Dasgupta, Papri; Poddar, Asok; Mukherjee, Manabendra; Manjunath, B.; Joy, P. A. (Materials Research Bulletin, 2018)
Single phase monoclinic La2Ni1-xMnO6 (x = 0.2, 0.4, 0.8) compounds, henceforth, referred as LNCxMO (x = 0.2, 0.4, 0.8) have been prepared by Sol-gel technique. The structural study and redox titration suggest that the samples are both La and O deficient. The generated atomic models using Rietveld refined structural parameters show octahedral distortion In the double perovskite structure. X-ray photoelectron spectroscopy (XPS) study has been used to determine the predominant valence states of Ni, Mn and Co ions. LNCxMO (x = 0.2, 0.4) are found to be Heisenberg ferromagnets whereas LNC0.8MO is a phase segregated system. In LNC0.4MO and LNO0.8MO, at temperatures above T-c, chi(-1)(T) curve shows the characteristics of Griffiths phase. The study of ac susceptibility and Isothermal remanent magnetization (IRM) discard the possibility of any glassy state at low temperatures. The antiphase boundaries (APBs), antisite disorders (ASDs) and oxygen vacancies play important roles in this system.

Thermal conductivity studies on magnetite nanofluids coated with short-chain and long-chain fatty acid surfactants - Lenin, R.; Dadwal, A.; Joy, P. A. (Bulletin of Materials Science, 2018)
The effect of the length of surfactant molecules on the surface of the nanoparticles on the thermal conductivity of nanofluids is studied. Magnetite (Fe3O4) nanoparticles of comparable sizes are stabilized with short-chain capric acid (C9H19COOH) and long-chain stearic acid (C17H35COOH) molecules. Thermal conductivity of the two surfactant-coated magnetite nanoparticles dispersed in toluene is measured as a function of the concentration of the particles in the fluids and in the presence of a magnetic field. Studies showed that the critical concentration for thermal conductivity enhancement is lower for stearic-acid-coated fluid as compared with the capric-acid-coated fluid. Comparable enhancement in the thermal conductivity is observed at higher concentrations of the particles. Relatively larger enhancement in the thermal conductivity is observed for the capric-acid-coated fluid in a magnetic field. The difference in the enhancement in the thermal conductivity, depending on the chain length of the surfactant, is explained in terms of the inter-particle magnetic interactions and formation of clusters.

Effect of co-substitution of Co2+ and V5+ for Fe3+ on the magnetic properties of CoFe2O4 - Anantharamaiah, P. N.; Joy, P. A. (Physica B: Condensed Matter, 2019)
Different chemical compositions in Co1+2xVxFe2-3xO4 (0 ≤ x ≤ 0.1) have been synthesized by the conventional solid-state reaction method and processed under identical conditions. The materials are investigated to assess the impact of change in the oxidation states of metal ions on structural and magnetic properties of cobalt ferrite. Rietveld refinement of the X-ray diffraction patterns revealed a single phase nature of all compositions with cubic spinel structure. The cubic lattice parameter was found to decrease non-linearly from 8.393 Å for x = 0 to 8.377 Å for x = 0.1, due to the effect of ionic size and valency of the substituted metal ions. Sintered co-substituted compositions exhibited smaller grains against unsubstituted counterpart, due to low melting point of raw material V2O5. Strong experimental evidence of V substitution for Fe at the tetrahedral sites of the spinel ferrite has been extracted from the Raman spectral analysis. Saturation magnetization (Ms) was observed to decrease from 452 kA/m for x = 0–411 kA/m for x = 0.1. Coercivity (Hc) and magnetocrystalline anisotropy (K1) were also found to follow the same trend. Variation of the structural and magnetic parameters is attributed to the changes in the oxidation state of Co from 2 + to 3 + as it is confirmed from the results of XPS analysis.

Large enhancement in the magnetostriction parameters of the composite of CoFe2O4 and CoFe1.9Ga0.1O4 - Anantharamaiah, P. N.; Joy, P. A. (Materials Letters, 2019)
A new strategy to enhance the magnetostriction parameters of cobalt ferrite (CoFe2O4) is illustrated. A composite comprising of nanocrystalline CoFe2O4 and bulk CoFe(1.9)Ga(0.1)O(4 )powders were mixed together then compacted and sintered at 1450 degrees C for 10 min. For a composite of 70 wt% CoFe2O4 and 30 wt% of CoFe(1.9)Ga(0.1)O4, maximum magnetostriction coefficient (lambda(max)) of -350 ppm has been obtained at lower magnetic field which is nearly 20% and 65% higher than that obtained for CoFe2O4 and CoFe1.9Ga0.1O4, respectively. Moreover, the composite exhibited higher strain sensitivity [d lambda/dH](max )of -2.6 x 10 (9) A(-1) m against the individual components of the composite. (C) 2018 Published by Elsevier B.V.
Keywords: Ceramics; Composite materials; Magnetic materials

Magnetic parameters of SrFe12O19 sintered from a mixture of nanocrystalline and micron-sized powders - Shashanka, H. M.; Anantharamaiah, P. N.; Joy, P. A. (Ceramics International, 2019)
Obtaining higher magnetic parameters is essential for high-power sintered strontium ferrite (SrFe12O19) for various applications. A novel approach has been made to improve the magnetic parameters of sintered strontium ferrite by making self-composites from nano and micron-sized powders. Powders with two different weight ratios (50 wt% nano:50 wt% micron and 75 wt% nano:25 wt% micron) were mixed together, compacted and sintered at 1200 degrees C for 1 h. For a self-composite of 75 wt% nano and 25 wt% micron-sized powders, coercivity (H-c) of 3076 Oe has been obtained, larger than the values for the sintered compacts from the component powders. The present study suggests that the magnetic parameters of sintered SrFe12O19 can be improved by making self-composite comprising of nanocrystalline and micron-sized powders.
Keywords: Ceramics; Magnetic materials; microstructures; Self-composites; strontium ferrite

Magnetic properties of sintered CoFe2O4-BaTiO3 particulate magnetoelectric composites - Mohan, S.; Joy, P. A. (Ceramics International, 2019)
The magnetic properties of sintered particulate magnetoelectric CoFe2O4 - BaTiO3 composites have been studied. The particulate composites are sintered in the temperature range 1000-1300 degrees C, for a short duration of 10 min. The magnetic transition temperature (T-c) of CoFe2O4 is found to decrease with increasing the sintering temperature and sintering time, as well as on increasing the BaTiO3 content in the composites. Similarly, a reduced saturation magnetization at room temperature, compared to that expected for the CoFe2O4 content, is also observed. Powder X-ray diffraction studies showed the presence of the impurity phase related to the hexagonal ferrite BaFe12O19 in all the composites. Ba2Fe2Ti4O13 is observed as a second impurity phase in the BaTiO3 - rich composites. The present studies suggest that the composition of the piezomagnetic (CoFe2O4) phase in the CoFe2O4 - BaTiO3 magnetoelectric composite is affected during the sintering process.
Keywords: composites; magnetic properties; Sintering

Raman and Na-23 solid-state NMR studies on the lead-free ferroelectrics Bi-0.5(Na1-xKx)(0.5)TiO3 in the morphotropic phase boundary region - Anjali, K.; Ajithkumar, T. G.; Joy, P. A. (Materials Research Bulletin, 2019)
The local structural changes, due to the substitution of the smaller Na+ by the larger K+ ion, in the lead-free piezoelectric ceramic compositions Bi-0.5(Na1-xKx)(0.5)TiO3 have been studied using Raman and Na-23 solid-state NMR spectroscopy. Different close compositions in the solid solution series Bi-0.5(Na1-xKx)(0.5)TiO3 (0 <= x <= 0.36, Delta x = 0.02) are studied in the morphotropic phase boundary (MPB) region arising from the different crystal structures of the end members Bi0.5Na0.5TiO3 and Bi0.5K0.5TiO3. Close correlations between the Raman and NMR parameters with the performance parameters of the system have been observed, suggesting the role of the local structural changes in determining these parameters. Raman and Na-23 NMR studies showed that the onset of the MPB region is at x = 0.16 and the MPB region corresponds to 0.16 <= x <= 0.24 where better performance parameters are observed.

Stealth emulsion based on natural rubber latex, core-shell ferrofluid/carbon black in the S and X bands - Vinayasree, S.; Nair, Ajalesh Balachandran; Mani, Manoj; Archana, V. N.; Joseph, Rani; Mohanan, P.; Joy, P. A.; Anantharaman, M. R. (Nanotechnology, 2019)
A lossy dielectric with an appropriate magnetic property is one of the requirements of a stealth material. The thickness of the absorber and the corresponding bandwidth of absorption are also other deciding factors that determine the choice of the material as microwave absorbers. A stable emulsion, which is lossy as well as magnetic, is promising, since it can be coated on surfaces with required thickness in the desired band. A magnetic nanofluidic emulsion serves the purpose. A microwave absorbing emulsion based on natural rubber latex with core-shell magnetic nanoparticles, based on superparamagnetic iron oxide nanoparticles (SPIONs), was developed. The effect of additives like carbon black on the bandwidth of absorption was also studied as a function of weight percentage of carbon black. The complex dielectric permittivity and magnetic permeability were evaluated using a vector network analyser in the S and X bands. Furthermore, these results were modelled using surface impedance equations. These investigations revealed that the incorporation of carbon black enhances the bandwidth of absorption and an emulsion with the required dielectric permittivity and magnetic permeability can be tailored for stealth applications.
Keywords: carbon black; core-shell nanoparticles; ferrofluid; microwave absorbing paint; natural rubber latex

Particle size effect in different base fluids on the thermal conductivity of fatty acid coated magnetite nanofluids - Dadwal, Arun; Joy, P. A. (Journal of Molecular Liquids, 2020)
The effect of particle size on the thermal conductivity of nanofluids is studied by dispersing myristic acid coated magnetite (Fe3O4) nanoparticles in two different base fluids; toluene and kerosene. Magnetite nanoparticles of three different sizes 4, 7 and 10 nm dispersed in toluene and kerosene showed a linear increase in the thermal conductivity with increasing concentration of the nanopartides, above a critical concentration. The critical concentration below which the thermal conductivity remained unchanged with the concentration of the nanopartides is found to be lower for the kerosene-based fluids. The variation of thermal conductivity with particle size is without any clear trend. However, within the measurement errors (+/- 1%), the toluene-based fluids showed a decrease in the thermal conductivity with increasing particle size, whereas the opposite trend is observed for the kerosene-based fluids. Also, the kerosene-based fluids at similar concentrations of the nanopartides showed relatively larger enhancement in the thermal conductivity than the toluene-based fluids. The observed role of the base fluid in enhancing the thermal conductivity is correlated with the difference in the solvent-surfactant interactions which in turn affect the interfacial thermal resistance at the particle-fluid interface. The thermal conductivity of the nanofluids in toluene and kerosene is also found to show different trends with the size of the particles in the presence of an external magnetic field. The difference in the enhancement of thermal conductivity of the fluids in a magnetic field is explained in terms of the differences in the magnetic dipolar interactions, clustering/ agglomeration, and magnetic characteristics of the samples as well as the characteristics of the base fluid. (C) 2020 Elsevier B.V. All rights reserved.

Synthesis, crystal structures, dielectric and magnetic properties of manganese sulfonyldibenzoates - Balendra; Singh, Bharti; Banday, Azeem; Tewari, Shailabh; Kumar, Vineet; Murugavel, Sevi; Joy, P. A.; Ramanan, Arunachalam (Crystengcomm, 2021)
{A systematic investigation of the system manganese(II) salt-H(2)SBA-auxiliary ligand-solvent successfully led to the isolation of six new multidimensional coordination polymers: [Mn-5(2-pic)(2)(DMA)(4)(SBA)(4)]center dot 4DMA (1), [Mn-3(pyzc)(2)(DMF)(H2O)(SBA)(2)]center dot DMF center dot H2O (2), [Mn-5(pyzc)(2)(DMA)(4)(SBA)(4)]center dot 4DMA (3), [Mn-5(mpyzc)(2)(DMA)(4)(SBA)(4)]center dot 4DMA (4), [Mn-2(phen)(2)(H2O)(SBA)(2)]center dot 2DMA (5) and [Mn-3(phen)(2)(SBA)(3)]center dot 5DMF (6), where SBA = 4,4'-sulfonyldibenzoate 2-pic = 2-picolinate